An Assessment on the contribution of smallholder maize irrigation farming to household income and food security in semi-arid region of Zimbabwe: case of Tokwane Ngundu Irrigation Scheme, Masvingo - Mushayi, Vadzanayi (BUSE, 2019)
The study was aimed at assessing the contribution of smallholder maize irrigation farming to household income and food security in Tokwane Ngundu in Masvingo District, Zimbabwe. Some research has been done in irrigation schemes but little is known about maize production in Tokwane Ngundu and how irrigating maize contributes to household income, this research will help the beneficiaries in irrigation schemes to improve maize productivity. Multistage sampling was used to purposively select study area and random sampling was used to choose 70 participants out of 88 households. Structured questionnaires, key informants’ interviews and passive observations were used to collect data. To explore challenges, descriptive statistics was used, multiple linear regression was used to determine factors affecting the contribution of maize to household income. Food security was assessed using Household Food Insecurity Access Score (HFIAS) and Household Food Access Prevalence (HFIAP). The higher the HFIAS the more the household is food insecure. Mismanagement of irrigation resources by irrigation scheme management, water unavailability and high-water costs, inputs unavailability and input costs, market availability were discovered to be the main challenges affecting maize production in the irrigation scheme. Area under production and age of household heads significantly affected the contribution of maize to household income at 5% significance level while average maize yield was significant at 10% significance level. The average HFIAS for the interviewees was 9.7 and ranged from 0 to 13. Most of the study participants (48.6%) were severely food insecure, while 42.9% were moderately food insecure, 5.7% were mildly food insecure and only 2.9% were food secure. The results clearly show that the majority of the interviewed maize irrigation farmers are food insecure meaning the irrigation scheme are not meeting the set objectives of producing excess food supplies to the nation. Irrigation farmers should get agricultural extension education, use improved hybrids of maize seeds, optimum fertiliser applications and recommended pesticide dilutions to improve maize yields. The researcher recommends that young farmers should get agriculture training and education to improve maize productivity. There is need for the provision of food aid within the scheme since some households were severely food insecure. Keywords: smallholder irrigation, irrigation scheme, household income, food security, food access.
Keywords: Maize production; Maize irrigation farming; Household income; Household food security; Irrigation scheme